Long-term gamma transcranial alternating current stimulation improves the memory function of mice with Alzheimer’s disease - Wu, Linyan; Cao, Tiantian; Li, Sinan; Yuan, Ye; Zhang, Wenlong; Huang, Liang; Cai, Chujie; Fan, Liming; Li, Long; Wang, Jingyun; Liu, Tian; Wang, Jue (Frontiers in Aging Neuroscience, 2022)
Background: The main manifestation of Alzheimer's disease (AD) in patients and animal models is impaired memory function, characterized by amyloid-beta (Aβ) deposition and impairment of gamma oscillations that play an important role in perception and cognitive function. The therapeutic effect of gamma band stimulation in AD mouse models has been reported recently. Transcranial alternating current stimulation (tACS) is an emerging noninvasive intervention method, and researchers have studied the intervention effect of tACS more from the perspective of clinical rather than animal experiments. Thus, the intervention mechanism of tACS has not been fully elucidated, and the course of treatment in clinical selection also lacks theoretical support. Based on this issue, we investigated the effect of gamma frequency (40 Hz) tACS at different durations in a mouse model of AD. Methods: We placed stimulating electrodes on the skull surface of 3-month-old APP/PS1 and wild-type control mice (n=30 and n=5, respectively). Among them, 20 APP/PS1 mice were divided into 4 groups to receive 20 min 40 Hz tACS every day for 1-4 weeks. The other 10 APP/PS1 mice were equally divided into two groups to receive sham treatment and no treatment. No intervention was performed in the wild-type control mice. The short-term memory function of the mice was examined by the Y maze. Aβ levels and microglia in the hippocampus were measured by immunofluorescence. Spontaneous electroencephalogram gamma power was calculated by the average period method, and brain connectivity was examined by cross-frequency coupling. Results: We found that the long-term treatment groups (21 days and 28 days) had decreased hippocampal Aβ levels, increased electroencephalogram spontaneous gamma power, and ultimately improved short-term memory function. The treatment effect of the short-term treatment group (7 days) was not significant. Moreover, the treatment effect of the 14-day treatment group was weaker than that of the 21-day treatment group. Conclusion: These results suggest that long-term gamma-frequency tACS is more effective in treating AD by reducing Aβ load and improving gamma oscillation than short-term gamma-frequency tACS.